Van de Hulst essay: Multiple scattering of waves by discrete scatterers and rough surfaces. (February 2019) - Tsang, Leung
Highlights: It is a great honor to be selected for the van de Hulst Light Scattering award in 2018. An obligation of the Award was that I gave a lecture at the 17th Electromagnetic and Light Scattering Conference in 2018, at College Station, Texas. Another obligation is the composition of this essay. I choose the topic "The Multiple Scattering of Waves by Discrete Scatterers and Rough Surfaces" and discuss it from my perspective. I acknowledge the advice and support from Professor Jin Au Kong, my PhD thesis advisor at MIT and Professor Akira Ishimaru, my mentor at University of Washington. Abstract: This essay is on the theories of multiple scattering of waves by discrete scatterers and rough surfaces. Applications of the theories are illustrated with emphasis on the remote sensing of the earth. A historical background is provided. The basic theories are based on solving Maxwell equations. We describe the physical results, analytical approaches and numerical approaches of the work of the author and his collaborators.